PENGARUH TINGKAT PENDIDIKAN, PENGETAHUAN AKUNTANSI, UMUR USAHA, PENGALAMAN USAHA TERHADAP PENGGUNAAN INFORMASI AKUNTANSI - Utomo, Mega Putri; Sembiring, Carolyn Lukita; Astriani, Devi (Jurnal Pendidikan Ekonomi (JURKAMI), 2023)
A good accounting information system can help large and small companies grow. MSMEs in Karawang Regency rarely use accounting data. It is common knowledge that MSME members lack the skills to utilize accounting data to manage their money well. This research aims to examine differences in demographic parameters including education level, accounting knowledge, business age and business experience in Karawang. The analytical method used in this research is a quantitative data analysis method using the multiple linear regression method. Owners of micro and small companies in the Karawang region of Indonesia registered with the Cooperative Service are represented in the research sample population. The sampling method was used to collect samples using the Slovin method. Hypothesis testing uses a partial test (t test) simultaneous test (f test) coefficient of determination test. This research shows that there is a relationship between level of education, level of accounting knowledge, age of business and use of accounting information. Partial and simultaneous test results show that business experience, education level, accounting knowledge, business age influence the use of accounting information